1993
DOI: 10.1111/j.1600-0773.1993.tb01640.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of β‐Adrenergic Agents on Human Neutrophil Granulocyte Activation with N‐Formyl‐methionyl‐leucyl‐phenylalanine and Phorbol Myristate Acetate

Abstract: 1) Optimal concentrations of beta 2-agonists decrease the human granulocyte generation of reactive oxygen intermediates in response to activation with FMLP by 40-60%, without affecting the response to PMA. 2) beta 2-Agonists modify the priming effect of FMLP on activation with PMA, but do not interfere with the priming effect of E. Coli lipopolysaccharide on activation with FMLP. 3) Isoprenaline have different effects on generation of reactive oxygen intermediates and cell aggregation in FMLP-activated granulo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 35 publications
2
7
0
Order By: Relevance
“…These results have been corroborated by other groups using cardiomyocyte models of cardiomyopathy and heart failure, suggesting that the ROS-␤ 2 AR link is physiologically significant and, if unregulated, may be involved in pathophysiological states (Li et al, 2010;Xu et al, 2011). It is noteworthy that the agonism of ␤ 2 AR in human neutrophils facilitates a decrease in formyl-Met-Leu-Phe-mediated ROS generation (Opdahl et al, 1993;Anderson et al, 1996;Barnett et al, 1997), and others have shown that ␤ 2 AR agonism specifically decreases only extracellular ROS from these cells (Kopprasch et al, 1997). Together, these results suggest that ␤ 2 AR agonism may have cell type-specific differential effects on modulating ROS levels.…”
Section: Introductionsupporting
confidence: 75%
“…These results have been corroborated by other groups using cardiomyocyte models of cardiomyopathy and heart failure, suggesting that the ROS-␤ 2 AR link is physiologically significant and, if unregulated, may be involved in pathophysiological states (Li et al, 2010;Xu et al, 2011). It is noteworthy that the agonism of ␤ 2 AR in human neutrophils facilitates a decrease in formyl-Met-Leu-Phe-mediated ROS generation (Opdahl et al, 1993;Anderson et al, 1996;Barnett et al, 1997), and others have shown that ␤ 2 AR agonism specifically decreases only extracellular ROS from these cells (Kopprasch et al, 1997). Together, these results suggest that ␤ 2 AR agonism may have cell type-specific differential effects on modulating ROS levels.…”
Section: Introductionsupporting
confidence: 75%
“…Theoretically, the use of drugs acting as 2 -adrenoceptor agonists might be a rational approach to control the excessive oxidant production, by stimulating the natural catecholaminedependent regulation of neutrophil activity. Although isoproterenol has been shown to inhibit the neutrophil respiratory burst [12,13], the widely used 2 -agonist salbutamol appears to be ineffective, at least using macrophages [14]. Moreover, the recently developed long-acting 2 -agonist salmeterol [15], possibly endowed with potential anti-inflammatory properties [16], was found to be incapable of inhibiting the respiratory burst in guinea pig eosinophils [17].…”
Section: Introductionmentioning
confidence: 99%
“…12 In animal models of acute lung injury, b 2 -agonists reduce pulmonary neutrophil sequestration. 13 14 In vitro b 2agonists reduce the production of oxygen free radicals from neutrophils and other inflammatory cells 15 16 and reduce inflammatory cytokine production. 17 In humans, inhaled salmeterol (long-acting b 2 -agonist) inhibited LPS-induced neutrophil influx, degranulation and tumour necrosis factor (TNF)a release.…”
mentioning
confidence: 99%